90.6k views
5 votes
Consider the sequence of steps to solve the equation: 3(x - 4) + 5x = 9x - 36

Given = 3(x - 4) + 5x = 9x - 36
Step 1= 3x - 12 + 5x = 9x - 36
Step 2> 3x + 5x - 12 = 9x - 36
Step 3 = 8x - 12 = 9x - 36
Step 4 8x - 8x - 12 = 9x - 8x - 36
Step 5 = 0 - 12 = x - 36
Step 6 -12 = x - 36
Step 7 -12 + 36 = x - 36 + 36
Step 8 = 24 = x + 0
Step 9 = 24 = x
Which property yields Step 4?

User Ali Kamal
by
6.2k points

2 Answers

6 votes

Answer:

Subtraction Property of Equality

Explanation:

User Mortymacs
by
6.1k points
4 votes

Answer:

Explanation:

Additive inverse using addition property of equality.

User Karema
by
6.3k points